Effectiveness and Limitations of Spiramycin for Toxoplasmosis During Pregnancy: A Systematic Review - Noor Laila Harkaningdyah; Salma Auliya Fatimah; Ayu Anggresti; Lavia Dinta Nur Pratiwi; Nabila Risti Rachmadi; Andi Desiah Pranada (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Toxoplasmosis is brought on by the protozoan parasite Toxoplasma gondii. Toxoplasmosis can be transferred from a mother to her fetus during pregnancy, resulting in congenital illness. Spiramycin is administered in the early stages as a kind of prophylaxis for the fetus and can be continued until delivery. If the fetus becomes infected, therapy is altered to a triple mixture of sulfadiazine, folinic acid, and pyrimethamine.Objectives: This article aims to comprehensively review spiramycin as a prophylactic measure for preventing vertical transmission of infection to fetuses and its limitations, including adverse effects.Methods: This study used a systematic review approach of publications indexed in Scopus, PubMed, ScienceDirect, and Web of Science databases from 2014 to 2024. It utilized the PRISMA flow diagram to guide the article selection process until a conclusion was reached.Results: Based on the predetermined inclusion and exclusion criteria and in accordance with the topic of this research objective, six research articles were suitable for review. Among the six reviewed articles, spiramycin is the first-line therapy for preventing vertical transmission of Toxoplasma gondii to the fetus. The most common side effect of using spiramycin in pregnant women is paresthesia.Conclusion: Spiramycin has an important role in preventing congenital toxoplasmosis, but it is not recommended for infected fetuses. Instead, combination therapy is superior for treating infections that have occurred in the fetus.